Liensinine reshapes the immune microenvironment and enhances immunotherapy by reprogramming metabolism through the AMPK-HIF-1α axis in hepatocellular carcinoma - Jiahao Liu; Xuan Zhang; Xiaofei Fan; Peng Liu; Ze Mi; Hongpei Tan; Pengfei Rong (Journal of Experimental & Clinical Cancer Research)
Abstract Background Hepatocellular carcinoma (HCC) is a leading cause of cancer-related mortality, with limited treatment options in advanced stages. Liensinine, a natural alkaloid derived from Nelumbo nucifera, has shown promise as an anticancer agent. However, its underlying mechanisms, particularly in modulating tumor metabolism and immune responses, remain poorly understood. This study aimed to investigate the antitumor effects of Liensinine in HCC, focusing on its ability to modulate metabolic pathways, immune responses, and the tumor microenvironment. Methods HCC cell lines (HUH7 and Hep1-6) were treated with Liensinine in vitro to assess cell viability, migration, proliferation, and apoptosis. Metabolic reprogramming was analyzed through RNA sequencing, Seahorse metabolic assays, and glucose/lactate measurements. The effects on immune cells were studied by treating THP-1 macrophages and peripheral blood mononuclear cells (PBMCs) with conditioned media from Liensinine-treated cells. In vivo, subcutaneous xenograft and orthotopic liver cancer models were used to evaluate the therapeutic efficacy of Liensinine combination with radiotherapy and immunotherapy. Results Liensinine inhibited HCC cell viability, migration, and proliferation, promoting apoptosis and shifting metabolism from glycolysis to oxidative phosphorylation. This metabolic reprogramming was linked to the activation of the AMPK-HIF-1α axis and increased ROS production. Furthermore, Liensinine induced Endoplasmic reticulum (ER) stress, as evidenced by elevated levels of CHOP and ATF4, which contributed to AMPK activation and suppression of HIF-1α. Liensinine reduced PD-L1 expression, enhanced M1 macrophage polarization, and promoted CD8 + T cell infiltration into tumors. In vivo, Liensinine significantly suppressed tumor growth, reduced vascular density, and reshaped the immune microenvironment by promoting M1 macrophage polarization. Combination therapy with Liensinine, radiotherapy, and immunotherapy resulted in synergistic effects, including enhanced tumor cell apoptosis, increased immune cell infiltration, and improved therapeutic efficacy. Conclusion Liensinine exerts potent antitumor effects in HCC by reprogramming tumor metabolism, inducing ER stress, enhancing immune responses, and modulating the TME. The combination of Liensinine with immunotherapy and radiotherapy significantly improves therapeutic efficacy, suggesting its potential as a novel treatment strategy for HCC. Graphical abstract